A Randomized Comparative Study of 24- and 6-Hour Infusion of Nafamostat Mesilate for the Prevention of Post–Endoscopic Retrograde Cholangiopancreatography Pancreatitis: A Prospective Randomized Comparison Trial. Issue 8 (September 2016) - Kim, Su Jin; Kang, Dae Hwan; Kim, Hyung Wook; Choi, Cheol Woong; Park, Su Bum; Song, Byeong Jun; Nam, Hyeong Seok
Abstract : Objectives: Although prolonged intravenous infusion (24 hours) of nafamostat mesilate is effective for the prevention of post–endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis, it requires hospitalization and is expensive. The aim of this study was to compare the efficacy of 24- versus 6-hour intravenous infusion of 20 mg nafamostat mesilate for the prevention of post-ERCP pancreatitis (PEP). Methods: A total of 382 patients who underwent ERCP were randomly assigned into 2 groups: 24 hours or 6 hours. In both groups, nafamostat mesilate (20 mg) infusion was initiated up to an hour before ERCP and continued for either 24 or 6 hours. Results: The overall incidence of pancreatitis was 2.4% (9/371). The rates of PEP following 24- and 6-hour infusion were 2.8% (5/179) and 2.1% (4/192), respectively ( P = 0.744). No significant difference was observed in the severity of pancreatitis between the groups. On multivariate analysis, increasing pancreatic duct cannulations (odds ratio, 1.685; 95% confidence interval, 1.036–2.741; P = 0.036) was identified as a statistically significant risk factor of PEP. Conclusions: No difference was found in the incidence of PEP regardless of the duration of nafamostat mesilate infusion. Therefore, 6-hour infusion of 20 mg nafamostat mesilate may be useful for the prevention of PEP in an outpatient setting.